Home-Dwelling Older Adults’ Day-to-Day Community Interactions: A Qualitative Study - Elodie Perruchoud; Armin von Gunten; Tiago Ferreira; Alcina Matos Queirós; Henk Verloo (Geriatrics, 2022)
Background: Many home-dwelling older adults present abnormal behaviours related to dementia or to non-dementia cognitive impairment (e.g., agitation, anxiety, apathy, etc.). Because many older adults live at home alone or are able to hide any signs of abnormal behaviours from others, the non-healthcare workers who interact with older adults on a daily basis are key actors in detecting those behaviours and orienting older adults towards appropriate support services. To the best of our knowledge, no studies to date have explored the daily interactions experienced between older adults and the various non-healthcare workers whom they regularly encounter in the community. This work aimed to identify the non-healthcare workers who are regularly in direct contact with older adults during their day-to-day activities and then develop specific training for these workers on the subject of abnormal behaviours among the elderly. Methods: This qualitative and ethnographic study asked 21 home-dwelling older adults aged 65 years old or more to answer open-ended questions. Sixteen had no self-reported cognitive impairments, and five had a probable or diagnosed slight cognitive impairment or mild-to-moderate dementia. A thematic analysis of the data was carried out. Results: The non-healthcare workers who spent the most time with older adults with and without reported cognitive impairments were those working in cafés or tea rooms and leisure or activity centres. Conclusions: In view of the significant amounts of contact between home-dwelling older adults and non-healthcare workers, it seems necessary and sensible to increase non-healthcare workers’ knowledge about abnormal behaviours, especially by offering them training. The proactive detection and identification of older adults’ abnormal behaviours by non-healthcare workers will ensure earlier care and reduce avoidable hospitalisations, institutionalisations and costs linked to geriatric healthcare.